Ulinastatin attenuates capillary leakage and suppresses FoxO1-dependent angiopoietin-2 in sepsis-associated acute lung injury via PI3K pathway - Yating Lv; Yanfei Meng; Haiying Rui; Tongqin Li; Jing Zhang; Jie Liu; Xin Ma; Jiaqi Wang; Yamin Yuan; Yujing Jiang; Xiaoxi Yan; Miaobo Li; et al. (PLoS ONE, 2026)
Sepsis-associated acute lung injury (SALI) is characterized by endothelial barrier dysfunction and capillary leakage. Ulinastatin (UTI), a serine protease inhibitor with recognized clinical benefits in sepsis, has been reported to protect endothelial function, but the underlying mechanisms remain incompletely defined. This study investigated the protective effects of UTI against SALI and its specific mechanism of action. We found that UTI attenuated lung injury and endothelial dysfunction in both cecal ligation and puncture (CLP)-induced septic rats and LPS-stimulated human umbilical vein endothelial cells (HUVECs). UTI treatment reduced the expression of angiopoietin-2 (Ang-2), a key mediator of vascular destabilization, and exerted similar protective effects on endothelial function as dexamethasone (DEX). Mechanistically, UTI was demonstrated to have a stable interaction and favorable binding affinity to PI3K by docking and activating the PI3K/Akt signaling pathway. This led to phosphorylation and subsequent nuclear export of the transcription factor FoxO1, thereby suppressing FoxO1-dependent Ang-2 transcription. The protective effects of UTI on capillary leakage and junctional protein integrity were abolished by the PI3K inhibitor wortmannin. In conclusion, our findings demonstrate that UTI alleviates SALI by disrupting an Ang-2-mediated vicious cycle via the PI3K/Akt/FoxO1 pathway, revealing a novel mechanistic insight into its therapeutic action against sepsis-induced vascular leakage.